2019
DOI: 10.1039/c9sc00410f
|View full text |Cite
|
Sign up to set email alerts
|

The full dynamics of energy relaxation in large organic molecules: from photo-excitation to solvent heating

Abstract: In some molecular systems, such as nucleobases, polyenes or sunscreens, substantial amounts of photo-excitation energy are dissipated on a sub-picosecond time scale. Where does this energy go or among which degrees of freedom it is being distributed at such early times?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 70 publications
3
77
0
Order By: Relevance
“…Regardless the exact S* origin, these results showed that there indeed is a correlation between energy dissipation (vibrational cooling, internal vibrational redistribution) and the S* signal in carotenoids [29] . Thus, studies of excited state relaxation pathways upon excess energy excitation represent a promising approach to reveal further details about energy dissipation/redistribution in carotenoids.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Regardless the exact S* origin, these results showed that there indeed is a correlation between energy dissipation (vibrational cooling, internal vibrational redistribution) and the S* signal in carotenoids [29] . Thus, studies of excited state relaxation pathways upon excess energy excitation represent a promising approach to reveal further details about energy dissipation/redistribution in carotenoids.…”
Section: Introductionmentioning
confidence: 87%
“…The short excited state lifetimes of carotenoids imply fast and efficient dissipation of absorbed energy both to molecular vibrations, generating hot states, and eventually to the environment [29] . This is especially important for long (N>12) carotenoids, for which the energy absorbed via the S 0 ‐S 2 transition (∼20000 cm −1 ) is non‐radiatively dissipated within ∼1 ps [17,30,31] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current view of the origin of the S∗ signal in solution points toward contributions from both a vibrational shoulder of S 1 and “hot” ground-state effects ( Balevičius et al., 2016 ; Ehlers et al., 2018 ). The hot ground-state contribution to the S∗ signal is probably a combination of long-lasting vibrational excitation and slow heat dissipation to the environment ( Balevičius et al., 2019 ). Even though a “hot” ground state is the inevitable product of rapid excitation quenching by S 1 , it is clearly not the origin of the 515 nm band.…”
Section: Discussionmentioning
confidence: 99%
“…Several spectroscopic methods, including infrared and ultraviolet absorption, Raman, jet-cooled laser-induced fluorescence, have been utilized to map out the whole series of vibrational quantum states of molecules in their ground and excited electronic states [43][44][45]. These multiple quanta properties are very important for numerous molecular processes such as chemical reactions [46,47], isomerization or inversion [48][49][50][51][52], as well as energy transfer during inelastic collisions proceeding along vibrational pathways that are governed by vibrational potential energy surfaces [53,54]. Development of spectroscopic approaches to reveal the whole vibrational (or electronic) potential surface is thus highly demanded and simple nonlinear spectroscopy probes may aid in this direction.…”
Section: Introductionmentioning
confidence: 99%